ASSOCIATION BETWEEN ATYPICAL DEPOLARIZATION IN CELLDYN 00 AND THE PRESENCE OF PLASMODIUM SPP IN BLOOD IN Dr. SOETOMO HOSPITAL SURABAYA - Nugraha, Jusak (Institute of Topical Disease Universitas Airlangga, 2011)
Background: Malaria is a parasitic disease worldwide with a high morbidity and mortality. A rapid and accurate method is needed to detect the presence of malaria parasites in blood. A flagging system atypical depolarization (atypdep) in CBC results from Cell-Dyn 3200 has been related with malaria infection. Materials and Methods: An observational cross sectional approach with 48 samples obtained from inpatients of the Dr.Soetomo Hospital, Surabaya. Samples were screened by Cell-Dyn 3200 analyzer for atypdep flagging in CBC. Positive samples were later confirmed by microscope to detect malaria parasites. results: From 48 samples with atypdep flagging, 7 samples were malaria positive on peripheral blood smear (13.1%). Most frequent atypdep flagging was seen in malignancy (18.7%), and approximately 54.6% of the samples were not accompanied by fever symptoms. Lekositosis and anemia each were found in 20 samples (41.6%) and thrombocytopenia in 33.3%. conclusion: The presence of atypdep flagging in Cell-Dyn 3200 does not necessarily indicate the existence of malaria or it could be said that atypdep flagging is not always associated with presence of malaria infection. The usage of an atypdep flagging in non-endemic areas such as Surabaya is just an alert sign to evaluate malaria infection rather than a screening method to detect malaria.